Pemeriksaan Tekanan Darah dan Konseling Gizi pada Siswa-Siswi SMAN 1 Gerung - Junendri Ardian; Baiq Fitria Rahmiati; M Zulfikar Alfariki; Wiwin Lastyana; Regina Pricilia Yunika (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Hypertension or high blood pressure is a condition characterized by an increase in systemic arterial blood pressure above the threshold/normal value (Giles et al, 2009). Diseases and deaths that were initially dominated by infectious diseases turned into non-communicable diseases. Implementation In its implementation, the community service program is carried out with the following methods: a. Counseling was carried out by means of lectures using power points accompanied by pictures and discussions with students about the definition, classification, causes, risk factors, prevention and early management of hypertension in adolescents. b. Demonstration and examination of blood pressure and nutritional counseling. C. Weighing and height of students. Measuring the success of the activity, the service team measured the participants' knowledge before and after receiving counseling by distributing pre-test and post-test questionnaires. Conclusion: Before counseling the students' knowledge was 20.0% and after being given counseling there was an increase in knowledge to 90.0%. This means that there is a significant change after being given counseling. The follow-up of the results of this community service is that similar blood pressure checks and nutritional counseling can be carried out in different places, so that more students know and understand about hypertension in adolescents.